2017
DOI: 10.1002/jcb.26177
|View full text |Cite
|
Sign up to set email alerts
|

Rhodopsin T17M Mutant Inhibits Complement C3 Secretion in Retinal Pigment Epithelium via ROS Induced Downregulation of TWIST1

Abstract: Rhodopsin mutations cause autosomal dominant form of retinitis pigmentosa (RP). T17M rhodopsin predisposes cells to endoplasmic reticulum stress induced apoptosis. However, the pathogenic role of T17M rhodopsin in RP is not completely understood. Complement C3 has a protective role in RP pathogenesis. This study aimed to investigate whether T17M rhodopsin regulates C3 secretion in retinal pigment epithelium. The human retinal pigment epithelial cell line (ARPE-19) was engineered to overexpress wide-type (WT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…(ii) Autocrine regulation of complement transcripts/secretion by complement complexes or cleavage products, which are only produced if the SNP is present, could be imaginable. Complement components or complement cleavage products can activate cellular signaling pathways via specific receptors [ 63 , 64 , 65 ], which can result in increased or reduced transcription of complement components by associated transcription factors [ 66 , 67 , 68 ]. As we showed the secretion of complement components and presents of complement activation products as well as of receptors in hpRPE cells an autocrine regulation of complement is speculatively possible.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) Autocrine regulation of complement transcripts/secretion by complement complexes or cleavage products, which are only produced if the SNP is present, could be imaginable. Complement components or complement cleavage products can activate cellular signaling pathways via specific receptors [ 63 , 64 , 65 ], which can result in increased or reduced transcription of complement components by associated transcription factors [ 66 , 67 , 68 ]. As we showed the secretion of complement components and presents of complement activation products as well as of receptors in hpRPE cells an autocrine regulation of complement is speculatively possible.…”
Section: Discussionmentioning
confidence: 99%
“…However, earlier studies reported reduced C3 and C4 levels and increased immune complexes in the sera from RP patients, and this reduced systemic complement activity appears to be related to poor disease prognosis (Heredia et al, ). The rhodopsin T17M mutation also reduces C3 secretion in RPE cells (Xiong et al, ), suggesting that some RP‐related genes may regulate complement expression/secretion by RPE cells. Humphries et al showed that C1q, the primary component of the classical pathway of the complement system, is a survival factor for cone cells, and C1q deficiency promoted photoreceptor death in Rho −/− mice, a mouse model of Leber's congenital amaurosis (LCA; Humphries et al, ).…”
Section: Targeting the Complement System In Retinal Degenerative Disementioning
confidence: 99%